Proceedings of the Fourteenth ACM Conference on Electronic Commerce 2013
DOI: 10.1145/2482540.2482553
|View full text |Cite
|
Sign up to set email alerts
|

Potential games are necessary to ensure pure nash equilibria in cost sharing games

Abstract: We consider the problem of designing distribution rules to share 'welfare' (cost or revenue) among individually strategic agents. There are many known distribution rules that guarantee the existence of a (pure) Nash equilibrium in this setting, e.g., the Shapley value and its weighted variants; however, a characterization of the space of distribution rules that guarantee the existence of a Nash equilibrium is unknown. Our work provides an exact characterization of this space for a specific class of scalable an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 48 publications
3
54
0
Order By: Relevance
“…Lemma 3. Applying the SV to a non-cooperative CSG makes the game potential for which an NE always exists [39] [24].…”
Section: Lemmamentioning
confidence: 99%
See 1 more Smart Citation
“…Lemma 3. Applying the SV to a non-cooperative CSG makes the game potential for which an NE always exists [39] [24].…”
Section: Lemmamentioning
confidence: 99%
“…Hence, we just use the CBBTC algorithm representing both. The results for the network power for all the algorithms are normalized to the average 24 Total no. of nodes in the network, |Q| The normalized network power is then denoted byP net (a) = P net (a)/P max in which P net (a)…”
Section: A Simulation Setupmentioning
confidence: 99%
“…We proceed to show a lower bound on the price of stability of Θ(nH n ) for any uniform cost sharing protocol. To prove this, we use a result of Gopalakrishnan et al [7,Theorem 1] who showed that the set of generalized weighted Shapley cost sharing protocols is the unique maximal set of uniform cost sharing protocols that is stable. To state their result, we first recall the definition of the generalized weighted Shapley cost sharing protocols [9].…”
Section: Price Of Stabilitymentioning
confidence: 99%
“…Proposition 12 (Gopalakrishnan et al [7]). For every budget-balanced, uniform and stable cost sharing protocol ξ there is a weight system w such that ξ is equivalent to the generalized weighted Shapley cost sharing protocol with weight system w.…”
Section: Price Of Stabilitymentioning
confidence: 99%
“…Precisely speaking, by designing proper utility functions to each agent, the overall welfare (or overall cost) is considered as the potential function. Then, the techniques developed for game theoretic control (GTC) are applicable to find pure Nash equilibriums, which provide candidates of optimal solutions [7], [8].…”
Section: Introductionmentioning
confidence: 99%